2019
DOI: 10.1128/aem.01701-19
|View full text |Cite
|
Sign up to set email alerts
|

Ammonia Oxidizers in High-Elevation Rivers of the Qinghai-Tibet Plateau Display Distinctive Distribution Patterns

Abstract: Ammonia-oxidizing bacteria (AOB) and archaea (AOA) as well as comammox catalyze ammonia oxidation. The distribution and biogeography of these ammonia oxidizers might be distinctive in high-elevation rivers, which are generally characterized by low temperature and low ammonium concentration but strong solar radiation; however, these characteristics have rarely been documented. This study explored the abundance, community, and activity of ammonia oxidizers in the overlying water of five rivers in the Qinghai-Tib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 50 publications
4
17
1
Order By: Relevance
“…The high proportion of bacteria over archaea found in the vermiculations is consistent with previous reports indicating that in terrestrial ecosystems nitrate stimulates the activity of ammonia-oxidizing bacteria, but not that of archaea (Meinhardt et al, 2018). In addition, Zhang et al (2019a) reported that bacterial amoA gene abundance was significantly higher than that of archaea due to the activity of cold adapted Nitrosospira in rivers from the Qinghai-Tibet Plateau. In this context, Zhang et al (2019b) showed that soil microbial communities were adapted to high nitrogen levels, strengthening the function of ammonia oxidation in order to deplete the excess of nitrogen.…”
Section: Discussionsupporting
confidence: 91%
“…The high proportion of bacteria over archaea found in the vermiculations is consistent with previous reports indicating that in terrestrial ecosystems nitrate stimulates the activity of ammonia-oxidizing bacteria, but not that of archaea (Meinhardt et al, 2018). In addition, Zhang et al (2019a) reported that bacterial amoA gene abundance was significantly higher than that of archaea due to the activity of cold adapted Nitrosospira in rivers from the Qinghai-Tibet Plateau. In this context, Zhang et al (2019b) showed that soil microbial communities were adapted to high nitrogen levels, strengthening the function of ammonia oxidation in order to deplete the excess of nitrogen.…”
Section: Discussionsupporting
confidence: 91%
“…Recent studies of ammonia oxidizing microbial communities based on amoA genes revealed that relative proportions of comammox Nitrospira , AOB and AOA are highly variable across environmental matrixes including both natural and engineered systems ( Table 1 ). While in most ecosystems (e.g., river water, grassland, agricultural and paddy soil) AOA or AOB were the dominating organisms ( Kits et al, 2017 ; Zhang et al, 2019 ), comammox Nitrospira were found to mainly dominate in engineered systems ( Bartelme et al, 2017 ; Tatari et al, 2017 ), but also in some natural environments, such as specific freshwater lakes ( Shi et al, 2020 ) or the river water and sediments of the Yangtze River ( Liu et al, 2020 ). Contrary, no marine comammox organisms have been identified so far.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrosopolaris MAGs are most closely related (98.9–99.7% nucleotide similarity) to uncultured sequences from Antarctic soil (MH318339 and MH318307), grassland soil in Iceland (JQ403917 and JQ403913), and the Tibetan Plateau (GQ143258, GQ143220, GQ143135, KF004058, and MK987234) (Daebeler et al ., 2012; Xie et al ., 2014; Wang et al ., 2019; Zhang et al ., 2019) (Fig. 3b) .…”
Section: Resultsmentioning
confidence: 99%